ISSUES OF GAINING KNOWLEDGE AND THINKING THOROUGHLY IN THE WORKS OF IMAM AL-GHAZALI (ResearchJet Journal of Analysis and Inventions, 2021)
This article describes issues of gaining knowledge and thinking thoroughly in the works of Imam Al-Ghazali. In the course of the article, we will consider all the advantages of the works of Imam Al-Ghazali and the qualities of scientific terms in them.